B cell response to pneumococcal vaccines - Trück, J (2014)
Streptococcus pneumoniae is a significant cause of mortality and morbidity in both children and older adults, with infection resulting in invasive disease, pneumonia and otitis media. The inclusion of pneumococcal conjugate vaccines in routine infant immunisation programmes has had a major impact on disease rates. Vaccine-induced protection against pneumococcal infection is thought to be mediated by the generation of persistent serotype-specific functional antibodies and antigen-specific memory B cells, the latter capable of generating a rapid secondary antibody response on re-exposure to antigen. Although many studies have investigated the immunogenicity of pneumococcal vaccines in different age groups by measuring serotype-specific antibodies, there is more limited information about the B cells underlying such an immune response. Important areas to investigate include the identity of the B cell subsets involved in antibody production and the potential link between memory B cells (BMEM) and persistent antibody production by long-lived plasma cells. In this thesis I have investigated in detail the immune response to pneumococcal vaccines given to children and adults by a variety of different methods. By examining the variability of a BMEM ELISpot method, it was shown that this assay is robust and reproducible and can be performed on fresh or frozen samples and in different laboratories. Using this technique, in a study of pre-school children, it was demonstrated for the first time that the level of pre-existing serotype 3-specific antibody is negatively correlated with, and may directly impair the BMEM response to a booster dose of 13-valent pneumococcal conjugate vaccine (PCV-13) containing serotype 3 glycoconjugate. In the same study, it was shown that antibody persistence against most vaccine serotypes can be expected until the age of 3.5 years. A novel antigen-labelling technique was used in a detailed kinetics study of antigen-specific B cell subsets in response to either PCV-13 or 23-valent pneumococcal polysaccharide vaccine in adults. The results of this study revealed distinct B cell subset response patterns that were observed in all study participants indicating that IgM BMEM seem to play a major role in the immune response to pneumococcal vaccines. In addition, in the same study, genome wide analysis of gene expression was performed and it was shown that vaccination with either a pneumococcal conjugate or polysaccharide vaccine results in a marked difference in numbers of differentially expressed genes 8 days following vaccination. A further tool likely to be of use in investigating B cell responses is the analysis of the antibody repertoire using next-generation sequencing techniques. In order to test the ability of these methods to detect vaccine responses, a large dataset of high-throughput B cell receptor sequences was analysed and revealed convergence of antigen-specific complementary-determining region (CDR)3 amino acid (AA) sequences following vaccination and identified antigen-specific sequences. It was further demonstrated that for sequences directed against the H. influenzae type b (Hib) polysaccharide, diversity of immunoglobulin gene rearrangements is much greater than previously recognised. Frequencies of Hib-specific CDR3 AA sequences were linked with anti-Hib avidity indices highlighting the potential of this method as an alternative (functional) measure of vaccine immunogenicity. These data suggest that studying the B cells and antibody repertoire post-vaccination can give novel insights into the biology that underlies the immune responses.